The proposed role of ultrasound in the management of giant cell arteritis in routine clinical practice - Monti, S; Floris, A; Ponte, C; Schmidt, W; Diamantopoulos, A; Pereira, C; Vaggers, S; Luqmani, R (Oxford University Press, 2017)
Objective To develop and explore a protocol for using colour duplex sonography (CDS) in the routine care of GCA. Methods We tested CDS of temporal arteries and axillary arteries (AXs) on consecutive patients with suspected or established GCA, between July 2014 and September 2016. Results We assessed 293 patients [age 72 (10), female/male 196/97], of whom 118 had clinically confirmed GCA. Seventy-three percent of patients had already received high-dose glucocorticoids (GCs) for 17 (33) days. Among new referrals with <7 days of GC treatment (n = 55), the sensitivity of CDS was 63.3% (95% CI: 44%, 80%), specificity 100% (95% CI: 83%, 100%), positive predictive value 100% and negative predictive value 64.5% (95% CI: 53%, 74%). Sensitivity rose to 81.8% in patients with jaw claudication and high inflammatory markers. During the observation period, the rate of temporal artery biopsies decreased from 72 (42%) to 36 (25%) (P = 0.002). CDS was positive in 21% of 89 follow-up scans in asymptomatic individuals, compared with 37% in patients experiencing clinical flares. Over time, the number of halos reduced; only new or flaring patients showed a halo in four or more sites. The diameter of axillary halos reduced from referral [1.6 (0.4) mm] to follow-up [1.4 (0.2) mm, P = 0.01] or flares [1.4 (0.2) mm, P = 0.02]. Conclusion CDS provides high positive predictive value for diagnosing GCA and allows for a significant reduction in temporal artery biopsies. We explored the role of CDS in detecting flares and demonstrated a relationship to the extent of the distribution of halos, but not to their size.